2012
DOI: 10.1002/smj.2025
|View full text |Cite
|
Sign up to set email alerts
|

A resource‐based perspective on human capital losses, HRM investments, and organizational performance

Abstract: Reversing the focus on human capital accumulations in the resource-based literature, the authors examine the issue of human capital losses and organizational performance. They theorize that human capital losses markedly diminish the inimitability of human capital stores initially, but that the negative effects are attenuated as human capital losses increase. They argue further that these effects are more dramatic when human resource management (HRM) investments are substantial. As predicted, Study 1 shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
214
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 230 publications
(221 citation statements)
references
References 58 publications
(90 reference statements)
5
214
2
Order By: Relevance
“…Instead, he argues that the first instances of voluntary quits are the most damaging to performance (Shaw, Gupta, et al, 2005). In this view, a rise from zero turnover to moderate levels creates the most impactful loss of knowledge, skills, and abilities (Alexander et al, 1994;Shaw et al, 2013) and the most significant disruption-creating gaps in organizational communication networks (Shaw, Duffy, et al, 2005).…”
Section: The Importance Of Turnover Rate and Organizational Performanmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, he argues that the first instances of voluntary quits are the most damaging to performance (Shaw, Gupta, et al, 2005). In this view, a rise from zero turnover to moderate levels creates the most impactful loss of knowledge, skills, and abilities (Alexander et al, 1994;Shaw et al, 2013) and the most significant disruption-creating gaps in organizational communication networks (Shaw, Duffy, et al, 2005).…”
Section: The Importance Of Turnover Rate and Organizational Performanmentioning
confidence: 99%
“…A fourth view is a classic contingency model that originated in the strategic HRM literature. Arthur (1994) argued and found that the relationship between turnover rates and performance was moderated by how much the organization had invested in its people (see also Guthrie (2001) and Shaw et al (2013)). High investment organizations tend to perform better, but suffer greater productivity loss via turnover than organizations that invest little in their people.…”
Section: The Importance Of Turnover Rate and Organizational Performanmentioning
confidence: 99%
See 2 more Smart Citations
“…Precisely identifying its components, let alone putting them together, is difficult, and may make the replication of human capital impossible (Shaw, Park & Kim 2013). The more firm-specific the components of human capital are, the more difficult it is to imitate them and the more valuable they are for companies (Hatch & Dyer 2004).…”
Section: The Importance Of Human Capital In Entering New Marketsmentioning
confidence: 99%